Correction to: Filling the data gap on CGRP mAb therapy in low- to middle-income countries in Southeast Asia: insights from a real-world study in Thailand (The Journal of Headache and Pain, (2024), 25, 1, (150), 10.1186/s10194-024-01859-3) - Anukoolwittaya, Prakit; Hiransuthikul, Akarin; Pongpitakmetha, Thanakit; Thanprasertsuk, Sekh; Rattanawong, Wanakorn (My University, 2025)
In this article reference 13 was Asawavichienjinda T, Imruetaijaroenchoke W, Phanthumchinda K (2020) Thai-version Migraine Disability Assessment (MIDAS) questionnaire: concurrent validity, test-retest reliability, internal consistency, and factors predictive for migraine-related disability. Asian Biomed (Res Rev News) 14(4):139–150 but it should have been Vongvaivanich K, Yongprawat T, Jindawong N, Chansakul C (2018) Test-Retest Reliability of the Thai Migraine Disability Assessment (Thai-MIDAS) Questionnaire in Thai Migraine Patients. Bangk Med J 14(1):10–10. The original article has been updated. The authors would like to apologize for any inconvenience caused.